Lattice and spin polarons in two dimensions - Zhao, Yang (2011)
A variational approach is employed to compute the wave function of a single polaron for a two-dimensional Holstein Hamiltonian with arbitrary forms of linear particle–boson interactions and boson dispersion relations. The Toyozawa ansatz is utilized, and generalizations to multiple polarons are outlined. Applications are made to model superradiance in pseudoisocyanine bromide J-aggregates, and to calculate quasiparticle dispersion of an itinerant hole in a two-dimensional antiferromagnet.